2022
DOI: 10.1002/admi.202201473
|View full text |Cite
|
Sign up to set email alerts
|

Phase Control of Cobalt Selenide: Unraveling the Relationship Between Phase Property and Hydrogen Evolution Catalysis

Abstract: electric or solar energy as a driving force is a promising measure to realize the generation of green energy source. [1,2] However, electro-and photocatalytic hydrogen evolution reaction (HER) both confront a big challenge regarding the conversion efficiency and economical cost. [3][4][5][6] There are two general concerns for the two mentioned HER pathway, that is the low charge transport efficiency and surface reactivity. [7][8][9] Therefore, material design to overcome the general shortcomings for HER is urg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Based on all the above characterization and observed HER results, it is evident that both the catalysts based on CoSe 2 polymorphs (o-CoSe 2 and c-CoSe 2 ) despite their differing crystal structures and morphologies exhibit comparable HER performance. As per previous reports, CoSe 2 -based HER electrocatalysts with the same morphology but different crystal structures have resulted in markedly different HER activity that is attributed to their different electronic structure and hydrogen adsorption energy at the Co sites . In another instance, the HER performance of orthorhombic CoSe 2 is also reported to be morphology dependent because of the different electrochemically active surface areas they offered resulting in dissimilar reaction rates .…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…Based on all the above characterization and observed HER results, it is evident that both the catalysts based on CoSe 2 polymorphs (o-CoSe 2 and c-CoSe 2 ) despite their differing crystal structures and morphologies exhibit comparable HER performance. As per previous reports, CoSe 2 -based HER electrocatalysts with the same morphology but different crystal structures have resulted in markedly different HER activity that is attributed to their different electronic structure and hydrogen adsorption energy at the Co sites . In another instance, the HER performance of orthorhombic CoSe 2 is also reported to be morphology dependent because of the different electrochemically active surface areas they offered resulting in dissimilar reaction rates .…”
Section: Resultssupporting
confidence: 54%
“…As per previous reports, CoSe 2 -based HER electrocatalysts with the same morphology but different crystal structures have resulted in markedly different HER activity that is attributed to their different electronic structure and hydrogen adsorption energy at the Co sites. 27 In another instance, the HER performance of orthorhombic CoSe 2 is also reported to be morphology dependent because of the different electrochemically active surface areas they offered resulting in dissimilar reaction rates. 31 Furthermore, Yang's group reported that CoSe 2 /HC as well as p-CoSe 2 @HC (here HC represents hollow mesoporous carbon nanospheres) with the same crystal structure (mixture of orthorhombic and cubic phases) and similar nanoparticle-like morphology can exhibit different HER performances due to presence of different number of active sites.…”
Section: Structural and Morphological Characterizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inherent properties of CoSe 2 endowed it with high electronic conductivity and proton adsorption ability, while its low cost and stable chemical properties made it a potential substitute for noble metals. 31–34 As reported by Jia et al , a binary CoSe 2 /g-C 3 N 4 composite photocatalyst was rationally fabricated, 35 in which the presence of CoSe 2 significantly facilitated charge transfer and the separation of photoinduced charge, contributing to elevated photocatalytic hydrogen evolution activity and excellent stability. However, most of the preparation processes required high-temperature heat treatment, which contradicted the concept of energy conservation and possessed certain risks.…”
Section: Introductionmentioning
confidence: 94%